HERMENEUTIKA GADAMER DALAM KAJIAN HUKUM - Lina Kushidayati (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2014)
Hermeneutic is a tool of analysis in social science that may be used in the study of law including Islamic Law. This article discucces about Hans-George Gadamer and his concept on hermeneutic. According to Gadamer, understanding in an important aspect of human and being that can be understood in languange. The law as being thus may be understood using hermeneutical concept proposed by Gadamer. The law as text cannot be separated from the horison surrounding it. Keywords: Hermeneutic, Gadamer, Law